2013
DOI: 10.1242/jcs.136515
|View full text |Cite
|
Sign up to set email alerts
|

Tubulin-binding cofactor C domain-containing protein TBCCD1 orchestrates cytoskeletal filament formation

Abstract: SummaryTBCCD1 is an enigmatic member of the tubulin-binding cofactor C (TBCC) family of proteins required for mother-daughter centriole linkage in the green alga Chlamydomonas reinhardtii and nucleus-centrosome-Golgi linkage in mammalian cells. Loss of these linkages has severe morphogenetic consequences, but the mechanism(s) through which TBCCD1 contributes to cell organisation is unknown. In the African sleeping sickness parasite Trypanosoma brucei a microtubule-dominant cytoskeleton dictates cell shape, inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 37 publications
1
35
0
Order By: Relevance
“…Moreover, dis initial cells were markedly larger than the wild-type equivalents and their Golgi network was more abundant and fragmented (shorter cisternae). Increased cell size and disorganization of the Golgi apparatus have been observed in TBCCd1-depleted human and trypanosome cells (Gonçalves et al, 2010;André et al, 2013). The role of TBCCd1 in regulating organelle positioning and microtubule and Golgi architecture, highlighted by our study, can therefore be traced back to the crown divergence of the major eukaryotic groups, more than a billion years ago (Eme et al, 2014).…”
Section: Dis Encodes a Tbcc Domain Protein With A Conserved Role In Imentioning
confidence: 57%
See 3 more Smart Citations
“…Moreover, dis initial cells were markedly larger than the wild-type equivalents and their Golgi network was more abundant and fragmented (shorter cisternae). Increased cell size and disorganization of the Golgi apparatus have been observed in TBCCd1-depleted human and trypanosome cells (Gonçalves et al, 2010;André et al, 2013). The role of TBCCd1 in regulating organelle positioning and microtubule and Golgi architecture, highlighted by our study, can therefore be traced back to the crown divergence of the major eukaryotic groups, more than a billion years ago (Eme et al, 2014).…”
Section: Dis Encodes a Tbcc Domain Protein With A Conserved Role In Imentioning
confidence: 57%
“…RP2 is also thought to be involved in microtubule assembly but the role TBCCd1 is less clear. Phenotypic analyses have shown that TBCCd1 plays an important role in positioning organelles within the cell in diverse organisms (Feldman and Marshall, 2009;André et al, 2013), but the molecular mechanism through which this protein acts is unclear and may not involve direct effects on microtubule dynamics (Gonçalves et al, 2010). These previous studies prompted us to compare intracellular features of germinating dis initial cells with those of the wild type.…”
Section: Dis Encodes the Conserved Protein Tbccd1mentioning
confidence: 99%
See 2 more Smart Citations
“…The TbMORN1 (40 kDa) molecules in the complex are arranged in a linear macromolecular filament of ϳ0.2 by 2 m whose posterior end is tightly coiled around the FPN, producing an overall fishhook-shaped morphology (13). At least nine other proteins are known to partially or wholly associate with this complex: TbLRRP1, TBCCD1, and seven currently uncharacterized proteins identified in a screen using proximity-dependent biotinylation (14)(15)(16). Both the TbMORN1 filament and the FPC are strongly associated with the microtubule-based cytoskeleton.…”
mentioning
confidence: 99%